1977
DOI: 10.1007/bf00562899
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical potassium excretion in response to aldosterone antagonists

Abstract: The activity of two aldosterone antagonists in reversing the urinary electrolyte changes induced by the mineralocorticoid fludrocortisone was examined in healthy subjects. Between 2-10 h after treatment there were dose-related increases in sodium excretion and the urine log 10 Na/K ratio, but no significant changes in urine volume, potassium concentration, or potassium excretion. Between 12-16 h after treatment there were dose-related increases in urine sodium excretion and the log 10 Na/K ratio. Unexpectedly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…As in studies using the dose ratio approach (McInnes et al, 1981;Ramsay et al, 1977a), an acceptable estimate of relative potency for potassium excretion was precluded although a statistically valid estimate was possible for urinary potassium concen- (Ramsay et al, . 1977b.…”
Section: Discussionmentioning
confidence: 99%
“…As in studies using the dose ratio approach (McInnes et al, 1981;Ramsay et al, 1977a), an acceptable estimate of relative potency for potassium excretion was precluded although a statistically valid estimate was possible for urinary potassium concen- (Ramsay et al, . 1977b.…”
Section: Discussionmentioning
confidence: 99%
“…If the urine flow rate does affect potassium excretion we must assume that spironolactone, function ally, affects the tubule proximal to the potassium excre tory site. A consequence of the theory of Ramsey et al [12] is that calculated proximal sodium reabsorption in our patients might be slightly underestimated. We conclude from our observations on CH20 /D D and on 24-hour potassium excretion that spironolactone inhibits sodium reabsorption at a site situated proximal to the localiza tion of the sodium/potassium and/or potassium excre tory site.…”
Section: Discussionmentioning
confidence: 99%
“…Ramsay et al [12] examined healthy subjects, who were pretreated with fludrocortisone, during aldosterone antagonists. They suggested that the initial kaliuretic effect was urine flow rate-and not natriuresis-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Synthesis of the title compounds is outlined in Scheme I. Dibenzothiophene-l-carboxylic acid (4) was prepared from 2-allylbenzo [6]thiophene and ethyl di-chloroethoxyacetate3 according to published methods. 4 It was converted to the acid chloride and reacted with 2amino-2-methylpropanol, yielding an hydroxyamide. Cyclization with thionyl chloride produced the oxazoline 5.…”
Section: Methodsmentioning
confidence: 99%